Stand-Alone, Low Probability of Detection Positioning for Small Airborne Vehicles Using Commercial SDRs - Arnaldo J. Sans; John M. Willis; Charles F. Barry; Marc Weiss; Satheesh Bojja Venkatakrishnan; John L. Volakis (IEEE Journal of Microwaves)
This paper presents the design, development, and prototyping of a stand-alone, low probability of detection (LPD) positioning network using commercially-available software-defined radios (SDRs). The network is intended for supplying positioning coordinates and is comprised of four receivers and a transmitter. For testing, a small drone was flown within a set range, carrying a payload with the transmitter and a high-precision microelectromechanical systems (MEMS) clock. The transmitter asynchronously sends timing data in a spread spectrum format, as frames, to the four receivers that despread and demodulate the encoded signals in real time. By using timestamps, the receivers calculate the time of arrival (TOA) and estimate both 2-D and 3-D positioning. Comparisons with the drone’s GPS flight paths is done to reveal average root mean square (RMS) positioning errors of 4.01, 4.27, and 9.57 in X, Y, and Z.